Superhydrophobic ceramics from surface modification (Research, Society and Development, 2022)
Superhydrophobic coatings attract attention due to their wide applications. However, most chemical substances and components used for their manufacture are generally harmful to the environment and have a high cost, which makes their application difficult. The purpose of this research is to develop super-hydrophobic coatings for ceramic substrates, prioritizing the use of eco-efficient materials. The ceramic substrate used in this study was the fired tile without vitrification, because it has a rough surface suitable for the deposition of the obtained coatings. The manufacture of super-hydrophobic coatings was made using sustainable and low-cost materials, which makes their use viable.